Proceedings of the 13th Koli Calling International Conference on Computing Education Research 2013
DOI: 10.1145/2526968.2526982
|View full text |Cite
|
Sign up to set email alerts
|

Computer science students' causal attributions for successful and unsuccessful outcomes in programming assignments

Abstract: While some students excel in introductory programming courses, others find the course to be significantly challenging and demanding. The way that students reason about the factors that contribute to success or failure may affect their self-efficacy, motivation, future success and whether or not they persist in Computer Science (CS). What factors do students' perceive to cause successful or unsuccessful learning outcomes in first-year programming assignments? Such findings can assist us in identifying causal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…This is similar to a study of students' self-reflection on their learning process where many voluntarily attributed causes of success and failure to nondiscipline specific strategies such as time management, effort and planning [41]. However, discipline-specific strategies were also identified by students as causes for success or failure, such as the adoption (or lack of) design strategies, pre-assessment of programming tasks and understanding of concepts.…”
Section: Introductory Programming Researchsupporting
confidence: 72%
See 2 more Smart Citations
“…This is similar to a study of students' self-reflection on their learning process where many voluntarily attributed causes of success and failure to nondiscipline specific strategies such as time management, effort and planning [41]. However, discipline-specific strategies were also identified by students as causes for success or failure, such as the adoption (or lack of) design strategies, pre-assessment of programming tasks and understanding of concepts.…”
Section: Introductory Programming Researchsupporting
confidence: 72%
“…The literature so far identifies that students reported a range of factors that contribute to success and failure in learning to program, such as effort, ability, time management, planning and task difficulty [12,13,29,41]. These can be referred to as causal attributions [42,43] and can be sorted into factors pertaining to the causal locus (internal or external), which are factors associated with the self (e.g.…”
Section: Attribution Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This is evident in the increasing failure and dropout rates among novice programmers in their introductory programming courses (Bennedsen and Caspersen 2007;Yadin 2011;Watson and Li 2014;Horton and Craig 2015). Several studies had been conducted to pinpoint what could have contributed to these high attrition rates (Kori et al 2015;Simon et al 2006;Kinnunen and Malmi 2006;Gomes and Mendes 2007;Biggers et al 2008;Moström 2011;Mhashi and Alakeel 2013;Simon et al 2013;Adu-Manusarpong et al 2013;Vivian et al 2013), and one of the prominent reasons is the lack of problem-solving skills (Carbone et al 2009;Falkner and Falkner 2012). Results also showed that time management strategies, effort, and lack of design and programming ability were among the primary reasons for their struggles in programming (Vivian et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Computer self-efficacy (CSE) plays an important role in students' perceptions of their abilities to accomplish computer tasks and perform successfully in work and learning environments [3], [4]. Students with low SE may difficult to succeed in the computer course [5], [6]. To promote CSE of students, the study of Ref.…”
Section: Introductionmentioning
confidence: 99%